G3XMP2 INVESTIGATION OF AMINE INVERSION IN ANILINE AND ITS PARA ANILINES - K, CHANDRASEKARAN; D, MUNIRAJASEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: This article addresses the inversion dynamics of aniline and para-anilines by G3XMP2 theory and the effect of substituents on the inversion barrier. Methods: The composite G3XMP2 method is used to evaluate the structural parameter, inversion barrier of aniline and para anilines. Results: The investigation shows that the electron donating substituents increase the inversion barrier by mesomeric and hyper conjugative effects. Thus it favours a non-planar structure. Electron withdrawing substituents, however, promote the planar structure by strong inductive effects. Of all the ten substituents studied, amino group yields high inversion barrier and results in a non-planar configuration, while the nitroso group attains low inversion barrier and accounts for the planar structure of amine group. Conclusion: The study concludes that the structure of amine group in aniline molecule is non-planar and its degree of non-planarity is heavily altered by the substituents. Keywords: Inversion barrier, G3XMP2, Aniline, Amino group, Planarity